The engineering of stilbazolium/iodocuprate hybrids with optical/electrical performances by modulating inter-molecular charge transfer among H-aggregated chromophores. Issue 6 (26th February 2020) - Wu, Wei; Lin, Xiang-Ling; Liu, Qian; He, Yan; Huang, You-Ren; Chen, Bin; Li, Hao-Hong; Chen, Zhi-Rong
Abstract : Good electrical bistability performances in stilbazolium/iodocuprate hybrids stem from the better face-to-face π⋯π stacking interactions induced by the substituents with appropriate lengths and electronic natures. Abstract : The combination of D–π-A stilbazolium-type chromophores bearing ortho-N -alkyl substituents with iodocuprate resulted in three novel hybrids, these were, [(CMAMP)2 (CuI3 )(acetone)0.5 ] n (1 ), [(HMAMP)(Cu3 I4 )] n (2 ), and [(HMAHP)2 (Cu5 I7 )] n (3 ), which present natural quantum-well architectures with void spaces of quasi-2- D organic layers occupied by iodocuprate anions via C–H⋯I hydrogen bonds. The D–π-A stilbazolium dyes exhibit head-to-tail arranged H-aggregations with face-to-face π⋯π stacking interactions. Theoretical calculations suggest that the charge densities on the benzenes can be strengthened from the electron-withdrawing group (–CN) to the electron-donating group (–OH), and the –C2 H5 OH substituents on the ortho -N of the pyridines not only help to open up the band gaps, but also provide a steric effect for better face-to-face π⋯π stacking interactions. Therefore, HMAHP + in 3 possesses the strongest face-to-face π⋯π stacking interactions owing to the presence of a longer –C2 H5 OH group in the ortho -N position, and consequently, blue-shifted photoluminescence, a stronger photocurrent (0.28 mA), and a higher ON/OFF ratio (1.6 × 10 4 ) can be observed in 3 . In particular, electrical bistability performances can be observed in ITO/hybrids/poly (methyl methacrylate) (PMMA)/Ag devices, which are explained using Schottky emission, space-charge-limited current effect (SCLC) and Ohmic mechanisms. According to theoretical calculations, the band gap switching from the semi-conductor to the conductor (high resistance state (HRS) to low resistance state (LRS)) after trapping electrons is exclusively dominated by the π bonding and anti-bonding orbitals of the stilbazolium dyes, which indicates a future direction for the design of stilbazolium-containing memory devices.